Antagonism of RNA silencing in the yellow fever mosquito, Aedes aegypti , by the nsP2 protein of the prototype alphavirus - Adarsh K. Gupta; Michael R. Wiley; Kevin M. Myles (Proceedings of the National Academy of Sciences, 2026)
Alphaviruses establish persistent infections in mosquito vectors despite robust antiviral RNA interference (RNAi) pathways, suggesting that they employ mechanisms to counteract host immunity. We demonstrate that the nsP2 protein of Sindbis virus (SINV), the prototype alphavirus, functions as a viral suppressor of RNA silencing in Aedes aegypti mosquitoes. Using a SINV mutant (2V) that prevents cleavage at the nsP2–nsP3 junction, we show that proper proteolytic processing to release mature nsP2 is essential for efficient viral replication in mosquitoes with intact RNAi pathways. Replication defects in the 2V mutant were rescued in Dicer-2 ( Dcr-2 ) null mutant mosquitoes or by expressing the mature nsP2 protein. Biochemical assays revealed that recombinant nsP2 directly binds double-stranded RNA and inhibits Dicer-mediated processing into small interfering RNAs (siRNAs). Furthermore, mosquitoes infected with the 2V mutant exhibited higher ratios of virus-derived siRNAs per viral RNA compared to wild-type infections, confirming that mature nsP2 suppresses the RNAi response. Our findings provide compelling evidence that nsP2 antagonizes RNA silencing in mosquito vectors, representing a critical adaptation that facilitates alphavirus replication.